Pengaruh Kepemimpinan Transformasional terhadap Keberlanjutan Pelayanan Publik pada Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Muhammad Surya Imam; Boni Saputra (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2025)
The sustainability of public services is a central issue in government governance in the digital era, as the widespread adoption of service innovations is not always accompanied by the ability to sustain them. Nationally, the SPBE Index stands at only 2.3 out of 5, and although more than 70% of local governments have adopted digital innovations, only about 50% are able to sustain them. At the Population and Civil Registration Office (Disdukcapil) of Padang City, the RAPEL GAJI innovation, a program for delivering civil registration documents in collaboration with Grab, ceased in January 2025 due to a non-renewed contract, triggering a surge in service queues. This case demonstrates that service sustainability depends not only on technology but also on leadership. This study analyzes the influence of transformational leadership on the sustainability of public services at the Padang City Disdukcapil. Using an associative quantitative approach, 42 employees were selected from a population of 70 via simple random sampling using the Slovin formula, employing a validated instrument that measures four indicators of transformational leadership and three indicators of service sustainability. The results of the simple linear regression indicate a positive and significant effect, with R² = 0.562 (56.2%) and t-calculated = 6.444 > t-table = 2.021 at p < 0.001. The regression equation Y = 15.743 + 0.318X confirms that every one-unit increase in transformational leadership increases the sustainability of public services by 0.318 units. These findings justify strengthening transformational leadership capacity as a strategy to maintain the sustainability of public service innovation.